2013
DOI: 10.1039/c3sm51003d
|View full text |Cite
|
Sign up to set email alerts
|

Self-folding with shape memory composites

Abstract: Origami-inspired manufacturing can produce complex structures and machines by folding two-dimensional composites into three-dimensional structures. This fabrication technique is potentially less expensive, faster, and easier to transport than more traditional machining methods, including 3-D printing. Self-folding enhances this method by minimizing the manual labor involved in folding, allowing for complex geometries and enabling remote or automated assembly. This paper demonstrates a novel method of self-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(198 citation statements)
references
References 28 publications
(39 reference statements)
0
196
0
2
Order By: Relevance
“…The increased control over assembly, as well as the integration of electrical circuitry, mean this approach is well suited to the self-folding of functional devices such as grippers. In addition, we have previously demonstrated bidirectional folding with this approach with the addition of a second SMP layer [23], [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increased control over assembly, as well as the integration of electrical circuitry, mean this approach is well suited to the self-folding of functional devices such as grippers. In addition, we have previously demonstrated bidirectional folding with this approach with the addition of a second SMP layer [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…While we have previously achieved some angle control by varying the overall width of the resistive heating elements [23], [24], we also found the heating duration to be important. Thus, here we fixed the heating element width at six millimeters (which simplifies design) and controlled the fold angle by adjusting the duration of current application.…”
Section: Electrically Activated Foldingmentioning
confidence: 99%
See 2 more Smart Citations
“…This essentially reduces down into the earlier section on thermal triggers, with additional potential for control and integration [86,170]. Felton et al demonstrated this approaching using Joule heating to trigger a sequence of plates connected by SMP hinges to fold into both an origami crane [171] and a walking robot [172].…”
Section: Electrical and Magneticmentioning
confidence: 99%